IMPROVING STUDENTS’ LISTENING SKILLS BY USING THE GAP FILLING TASK WITH AUDIO- DIALOGUE - Said, Nursakinah Alsavirah; Jabu, Baso; Korompot, Chairil Anwar (Universitas Negeri Makassar, 2024)
The present research aims to improve students' listening skills by using the Gap Filling assignment with Audio-Dialogue. In order to assess how students, react when studying auditory materials that include short stories as a gap filler, this study uses quantitative methodologies. To assess their comprehension of short story audio, thirty-two students took listening assessments. The listening test evaluated things like massage and conclusions. The data was analyzed using the independent t-test and descriptive statistics. The results of the study show that using audio conversations for gap-filling exercises in the classroom can greatly improve students' listening skills. Students need to concentrate on recognizing This study aims to discover specific information in audio speech with a focus on particular listening skills such as key comprehension and employing contextual cues to understand message indicators and conclusions. Students are taught to sift through pertinent material and make pertinent deductions using the gap-filling technique, which is based on audio-dialogue. According to the study's findings, SMP Negeri 1 Minasatene students' listening abilities have improved when gap-filling activities including audio dialogue are used.